Suntye / Dani Irfan Mohamed Faidz - Mohamed Faidz, Dani Irfan (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
Suntye, what is suntye? Suntye is a tie-dye fashion which produces fashion items such as sweater. The word Suntye derives from the word "Santai" from the Malay word which represent the meaning of relaxion, cool, and fun. The Unique Selling Point of Suntye is the technique used in producing Fashion items. We focus on a lot of different techniques on how to dye the appearance of the fashion items. The tag line is "Expose Your Style". So why Expose Your Style? Expose Your Style reflects how the fashion can help boost your fashion sense and style by wearing Suntye. Suntye was establish since 2019 and still on going until now. The owner name of Suntye is Yzmeen and she is currently doing her Bachelor in UiTM Shah Alam. She started this company based on her passion and now she put all of her efforts into it. The successful rate of the company is quite slow due total of lack of promotional items. Basically the idea and concept for Suntye is catchy, fun, interesting and most importantly unique in comparison from other fashion styles. Suntye also use a lot of different technique to make sure it stand out from the competitors. Currently, this project highlight three types of sweater which is Blossom, Caramel, and Red Velvet. The competitors for this product would be Asly, Barang Boek and a lot more. For our international competitors will be Cotton On, HnM and a lot more. In conclusion the vision for Suntye is to make the world more colourful and also 'santai' to look at it. Not just that but also to make sure our product reach worldwide so that we can make everyone look like they are exposing their style with different technique and also with amazing colour. Santai, Expose your style.